Development of microprogation and Agrobacterium mediated transformation protocols for pineapple (Ananas comosus) VAR. MD2 / Nur Syazwani Hamid - Nur Syazwani , Hamid (2018)
In this study, a simple direct in vitro propagation protocol was established for pineapple variety MD2 by using sucker as explants until acclimatization. Shoots were initiated on semi-solid Murashige and Skoog (MS) medium containing 3 mg/L 6-benzylaminopurine (BAP) and 1 mg/L 1-naphathylacetic acid (NAA) before multiplied in MS liquid medium containing 2 mg/L BAP and 1 mg/L NAA. Shoots separated from multiple-shoot clusters started to root after three days on MS medium containing 30 g/L sucrose, 2 g/L gelrite, and 6 g/L charcoal. Significantly different data observed on photosynthesis rate, stomatal conductance, and transpiration rate for plants acclimatized after 42 days compared to 14 and 28 days. Hence, 42 days of acclimatized plants could be the appropriate period for transferring in vitro-derived plants into fields since similar patterns of morphology and physiology observed with field-grown plants. Whilst, transformation of A. comosus with Agrobacterium tumefaciens strain EHA105 harbouring pkYLX71 plasmid with ABR17 gene was conducted. Polymerase Chain Reaction (PCR) analysis was applied to confirm the presence of ABR17 gene in individual putative transformed A. comosus. Studies revealed that explants infected for 10 min and cultured on medium supplemented with 100 μM acetosyringone and co-cultivated for 1 day evoked high number of regenerant line (45) and positive putative transformants (22%). Integration of the gene in the genome A. comosus was visualized using Southern Blot analysis.